Sustainability-focused business curricula educating corporate sustainability professionals: A knowledge-based view from Italian universities - Carla Del Gesso; Paola Parravicini (Journal of Innovation & Knowledge, 2025)
In response to mounting sustainability challenges, integrating sustainability into business-related education has become crucial for preparing specialized professionals capable of advancing sustainable business models. Addressing key research gaps and building on the knowledge-based view (KBV), this study examines trends in the implementation of sustainability-focused business degree programs across Italian universities, offering insights into the role of business education in facilitating corporate sustainability knowledge acquisition. Statistical evidence reveals an unprecedented shift in Italian business curricula toward sustainability, characterized by an interdisciplinary approach that encompasses economic, environmental, social, and governance dimensions. Moderate evidence of a positive impact of these curricula on employability suggests an evolving labor market demand for corporate sustainability professionals. Qualitative findings highlight the targeted preparation of roles such as sustainability managers and business consultants, followed by sustainability-savvy accountants, managers in sustainable digital innovation, circular economy specialists, and a range of emerging niche positions. This study contributes novel insights to the literature by foregrounding the strategic role of universities in supplying corporate sustainability knowledge as a specialized resource that organizations can acquire to support the development of sustainable business models. It also offers practical insights that may inform efforts by universities and policymakers to reimagine business education strategies, effectively equipping the contemporary corporate world with the evolving expertise required to meet growing sustainability challenges.